Exploring the relationship between efficiency of inventory management and firm performance: an empirical research. (1st January 2015) - Elsayed, Khaled
Inventory–firm performance relationship is a fast growing research area that attracted considerable research attention in the literature of production and operations management. To date, published literature has not only produced mixed findings, but also focused on presenting empirical evidence from developed countries. Inconclusive evidence in prior work implies that more research is needed to determine the relationship between efficiency of inventory management and firm performance. Accordingly, this research aims to contribute to the literature by presenting empirical evidence regarding this relationship from Egypt as a developing country. The results reveal that efficiency of inventory management and firm performance are positively correlated. This finding is robust to the use of different estimation methods and alternative proxies for firm performance variable, as well as the inclusion of other covariates.